Study of fluvial water treatability using γ-polyglutamic acid based biopolymer coagulant - Campos, Valquíria; Domingos, Janaína M F; Anjos, Diego N Dos; Lira, Vivian S. (FapUNIFESP (SciELO), 2019)
Successful treatment of surface water for public use requires the evaluation of raw water and coagulant efficacy. The purpose of water treatment is to remove impurities, allowing its quality to be classified to meet the needs of the population. The conditions of urban rivers that flow though the city of São Paulo, which were already undergoing major transformations, particularly due to intense urbanization, have deteriorated further due to the precariousness of basic sanitation and increasing environmental pollution.This study focused on an analysis of the efficiency of PGα21Ca, a water purification product, in the treatment of Pinheiros River water, based on coagulation-flocculation and sedimentation tests. The biopolymer PGα21Ca reduced in the order of 100% the total phosphorus. The best sedimentation velocity for the coagulant under study was 1 cm min-1. The PGα21Ca performed well in the removal of turbidity and apparent color, with residual turbidity ​​of 1.84 NTU, 96.95% removal of apparent color, and little change in the pH of the medium.